ЎРТА ОСИЁ МЕЪМОРЧИЛИГИДА НАҚҚОШЛИК САНЪАТИНИНГ ТАРИХИЙ ВА ЗАМОНАВИЙ МОҲИЯТИ (Scientific journal of the Fergana State University, 2023)
The article provides information on the history of Central Asian ornamental art. The samples of the applied art of the Uzbek people which has two millennia-old history, are still amazed.